Usahatani Tanaman Pangan Dan Peternakan Dalam Analisis Ekonomi Di Petani Dipedesaan - Cut R. Adawiyah; S. Rusdiana (Jurnal Riset Agribisnis dan Peternakan, 2016)
The study was conducted in the village Mekarsari Cibatu Subdistrict, Garut regency, West Java, the research carried out by the method of field survey in 2013 using the 20 lawncarequestionnaire and crop farmers with agro-ecosystem of farmland, fields, fields, upland vegetables, and pulses. Secondary data from farmers and local primary data from the Department and from the results of research, then the primary data and secondary data already collected tabulated and analyzed descriptively, quantitative, and analytical writing economic. The purpose is intended to determine farm crops and livestock in economic analysis in the rural farmer. Results of this research that the is business of food crops is an essential business and livestock as the main business effort. The amount of labor to grow rice farming families around (208.5 Hok) corn around (208 Hok), peanuts around (175.5 Hok), and cassava around (161.22 Hok). For beef cattle business around (158, 5 Hok), goats (179 Hok) and sheep around (180.9 Hok). Contributions from businesses crop and livestock production have a very important role in meeting the needs of the family. Contributions from businesses crop and livestock production very have an important role to meet the needs of families. The results of net income from business paddy crops around Rp.4.220.750/year/farmer, corn around Rp.4.267.500/year/farmer and sheep around Rp.1.812.120/year/farmers, the highest farmer benefits from the efforts of food crops, whereas livestock business as diversification of crops and businesses pastime farmers of the business principal of agriculture.